ANALISIS BUTIR SOAL DAN KEMAMPUAN SISWA MENJAWAB TES UN DAN UAS GANJIL MATA PELAJARAN BIOLOGI KELAS XI SMAN/MAN DI KOTA MEDAN - Siti Salmah Lubis; Syarifuddin Syarifuddin; Herawati Dongoran (Jurnal Pelita Pendidikan, 2017)
The research aims to determine the ability of students to answer of National Exam question’s and Odd Semester Exams questions as well as to know the quality of National Exams Class XI Odd Semester Year 2012- 2016 and Odd Semester Exams academic year 2016/2017 based on experiments viewed from the cognitive aspects based on bloom's taxonomy, level of difficultness, distinguishing power, and reliability. The method in this research using quantitative descriptive method. Sample test question is 6 class XI MIA amounted to 238 students with cluster sample technique .. The object of research is a matter of National Exams Class XI Odd Semester Year 2012- 2016 and about UAS coming from 6 schools. The results showed that students are better able to answer the National Exams question’s compared with Odd Semester Exams based on the average score of students in answering Odd Semester Exams question’s is higher than the National Exams question. Based on the cognitive aspects of Bloom's taxonomy the distribution of Odd Semester Exams academic year 2016/2017 does not meet the proportion of balanced questions based on formulation C1 40% C2 20% C3 20% C4 10% C5 5% C6 5%. Based on the difficulties of the distribution of UN and UAS Problems Ganjil T.P 2016/2017 does not meet the criteria of a balanced question based on a difficult formulation 25% medium 50% and easy 25%. Based on the distinguishing power of the distribution of the question of National Exam and Odd Semester Exams academic year 2016/2017 not meet the criteria of a good question with the criterion of differentiating power 0,30 - 1,00 ≥ 85%. Criteria of differentiating power 0,30 - 1,00 on question’s of  National Exams 32%, Odd Semester Exams of MAN 1 Medan 36%, MAN 2 Medan Model 53%, SMAN 4 Medan 52%, SMAN 9 Medan 35%, SMAN 11 Medan 49 %, SMAN 18 Medan 23%. Based on the reliability, the problem of National Exams has low reliability (0.3) while the average Odd Semester Exams has high reliability (0.60-0.79).Keywords : Analysis, item test, National Exam, Odd Semester Exam